Traditional and higher order sliding mode control of MEMS optical switch - Keramati, Ehsan (2010)
MEMS optical switches are the switches in which microelectromechanical systems technique is used to fabricate tiny mirrors in order to reflect the light beams directly from one fiber optic to another. This thesis mainly focused on closed-loop control of MEMS optical switch. The purpose of the control system is that to control the position of the micro-mirror. It is important to note that the relation between applied voltage and position in the electro-static actuators is nonlinear. In addition to this inherently nonlinear nature, the accurate mathematical model of the system is hard to derive. Therefore, it is so crucial to choose a control approach that handles uncertainties and nonlinearities. Based on the above discussions, to control the position of the micro-mirrors the most appropriate approach is the so-called sliding mode control scheme which is the robust nonlinear method. Both traditional sliding mode (TSM) and higher order sliding mode (HOSM) algorithms have been applied to the system. In order to investigate the robustness of the proposed controllers, external disturbance and parametric uncertainty are exerted to the system. In HOSM control system, robust exact differentiator is used to estimate the time derivatives of the sliding variable. Tuning the parameters of the controllers is carried out by using particle swarm optimization (PSO) method instead of conventional try and error. Apart from the entire above mentioned discussions, TSM control scheme has a drawback called ‘chattering’. It is a harmful phenomenon caused either by switching imperfections or unmodelled dynamics of the system and limits the application of the TSM method in reality. Among all the methods that have been proposed to avoid chattering, HOSM algorithm is used in this work to eliminate this disadvantage. The results of the TSM method show that the controller stabilizes the output at the different desired reference signals. Time response of the system shows faster system rather than previous TSM control system, the settling time decreased from 2.4 (s) to 0.0019 (s). Moreover, the proposed TSM controller introduces smoother output compare to previous work. In term of robustness, the controller is robust against the uncertainties and disturbances. However, the main drawback of the TSM method, chattering, is clearly appeared in the control signal. On the other hand, implementing HOSM controller eliminated the mentioned drawback while it keeps the advantages of TSM method. Apart from chattering elimination, it should be noted that the HOSM controller improved the accuracy of the output compared to TSM control system; magnitude of the steady state error has been decreased from 3.54×10-8(m) to 4.34×10-10(m).